2019
DOI: 10.35631/ijepc.4330011
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Methods, Achievement and High Order Thinking Skills (Hots) Among Accounting Students in Secondary Schools in Malaysia

Abstract: The purpose of this study is to determine the correlation between Accounting teachers’ use of various teaching methods with achievement and high order thinking skills (HOTS) of Principles of Accounting students. Samples are formed four students from schools in the Batang Padang district in Perak, Malaysia. The objectives of the study are to determine the level of practice of teaching methods, student achievement, and HOTS, the difference of the variables based on gender and quantitative skills and the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Classroom learning activities conducted by teachers have exposed students to the form of HOTS questions and how to answer HOTS questions. This reseach findings are parallel with the findings of a study by Dogan (2016); Peng and Hamad (2018);Mat Norwani, Yusof, Yahya and Ismail (2019); Shukla and Dungsungnoen (2016); Arshad and Yasin (2015) who stated that the students' level of self-efficacy and HOTS is at a moderate level. However, the findings of the study are different from the findings of Farrand, Wild and Hilson (2016); Ichsan, Sigit, Miarsyah, Ali, Arif and Prayitno (2019); Saido, Siraj, Nordin and Al_Amedy (2015) who found that the students' level of self-efficacy and HOTS is at a high and weak level.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Classroom learning activities conducted by teachers have exposed students to the form of HOTS questions and how to answer HOTS questions. This reseach findings are parallel with the findings of a study by Dogan (2016); Peng and Hamad (2018);Mat Norwani, Yusof, Yahya and Ismail (2019); Shukla and Dungsungnoen (2016); Arshad and Yasin (2015) who stated that the students' level of self-efficacy and HOTS is at a moderate level. However, the findings of the study are different from the findings of Farrand, Wild and Hilson (2016); Ichsan, Sigit, Miarsyah, Ali, Arif and Prayitno (2019); Saido, Siraj, Nordin and Al_Amedy (2015) who found that the students' level of self-efficacy and HOTS is at a high and weak level.…”
Section: Discussionsupporting
confidence: 87%
“…Self-efficacy can drive a person's tendency to respond positively or negatively to an idea or situation. Diversity in teaching methods can increase students motivation and achievement (Mat Norwani, Yusof, Yahya & Ismail, 2019). Therefore, as a suggestion, the learning process in the classroom will be more meaningful if teachers can attract the interest and attention of students through effective teaching and learning activities of HOTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation